Perfectionism and sense of coherence among patients with eating disorders. (August 2014) - Petersson, Suzanne; Perseius, Kent-Inge; Johnsson, Per
Abstract Background: There is a substantial body of research on eating disorders and perfectionism. Also there are several studies on eating disorders and sense of coherence (SOC), but studies regarding all three subjects are sparse. Perfectionism and the degree of SOC are considered central and aggravating aspects of psychiatric conditions, not least in relation to eating disorders. Aims: The present study aimed to describe the relationship between perfectionism as operationalized by Garner in the Eating Disorder Inventory-2 and SOC as defined by Antonovsky in the SOC-29 scale. The hypothesis was that SOC should be negatively associated with perfectionism. Methods: Data from the two self-measuring instruments collected from 95 consecutively recruited eating disorder outpatients were analysed with descriptive and inferential statistics. Results: The patients in the present study scored consistently with other Swedish eating disorder samples on the Perfectionism subscale in the Eating Disorder Inventory-2 (EDI-P) and on the SOC-29, indicating a higher degree of perfectionism and weaker SOC than normal population groups. Perfectionism was significantly correlated to SOC. The correlation was negative, confirming the study hypothesis. The hypothesis was further confirmed in a subgroup analysis comparing patients with different degrees of SOC related to their EDI-P scores. Conclusions: Perfectionism is associated with SOC in patients with eating disorders. Clinical implications: The clinical implications derived from the study could be a recommendation to focus on the SOC in patients with an eating disorder with the hope of lowering the patients' perfectionism as well.